Linguistic Peculiarities of Contemporary Political Verbal Texts - Lomadze, Tamar (Actual Problems of Kartvelology, 2013)
The topic of our research is one of the main types of political text – an election discourse, which often turns out to be the main explanation of successful election campaigns. Pre-election text analysis enables us to focus our attention on linguistic aspects, to find out the key words and to study what terminology is applied in politics. In the presented article, we have analyzed two television appearances of one of the presidential candidates of the 2013 Presidential Elections - Giorgi Margvelashvili: the interview at the very beginning of the election campaign on the Georgian TV channel Rustavi 2, programme ‘Positsia’ (the Position) and one of his last programmes during his campaign again on Rustavi 2, programme – ‘Archevani’ (the Choice). We have identified and analyzed the linguistic peculiarities and style characteristic for Giorgi Margvelashvili. Our attempt was to find out whether the literary norms of the Georgian language are followed and how often the foreign terms are used. Besides, we drew particular attention to the linguistic inaccuracy and rhetoric devices that G. Margvelashvili applies in the abovementioned programmes. It is obvious that, apart from scientists and the media, politicians play an important role in preserving the purity of the language. Every single linguistic mistake made by politicians during their public appearances are immediately reflected on the language of the wide society.